Postoperative Protocols for Lower Extremity Free Flap Reconstructions: Literature Review and a National Survey of the United Kingdom's Major Trauma Centers - Glynou, Sevasti Panagiota; Georgiannakis, Ariadni; Ackling, Edward; Bystrzonowski, Nicola; Pafitanis, Georgios; Diver, Andrew (Journal of Reconstructive Microsurgery Open, 2024)
Background Evidence for postoperative care of lower extremity free flap reconstruction (LEFF) varies and is yet to be standardized, despite established guidelines by the British Orthopedic Association Standard for Trauma (BOAST-4). This study assesses postoperative protocols for LEFF clinical monitoring, warming, dangling, and compression in the United Kingdom's (UK) major trauma centers (MTCs).Methods An online questionnaire was distributed to consultant leads of all UK adult MTCs. Data requested the existence of a standardized protocol, intensity, and takeback of LEFF procedures and specific practices in clinical monitoring, warming, dangling, and compression. Analysis was performed in Excel.Results The survey was returned by 23 (79.3%) units and most (86.9%) had standardized LEFF monitoring protocols. Centers typically performed four to eight surgeries monthly and on average had 2.7 salvageable LEFFs in 2022. Clinical monitoring was common (>92%) and included color, capillary refill, and temperature assessment. Compression initiation varied between 45.5% (starting after day 7) and 40.9% (from days 3 to 5). Continuous compression was favored (78.3%), using pillows (88.9%). Dangling protocols begin between days 3 and 7, for 5 minutes (52.2%) with frequencies of three to four times daily (25–37.5%). The preferred tool for LEFF warming was the Bair hugger (82.6%) and the mean termination day for warming was 3.61.Conclusion The survey highlights the need for evidence-based and consensus in UK MTC protocols for LEFFs. We encourage ongoing research and collaborative efforts in creating an accepted protocol among MTCs that could be incorporated into the BOAST-4 guidelines for postoperative care standardization and improved patient outcomes.
Keywords: lower extremity; free flap; major trauma; protocol